Mitigation Plan for Adulterated Ayurvedic Herbs/Herbal Raw Drugs - Rana, Charan S; Rai, Rajiv K (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Adulteration of herbal raw drugs compromises efficacy and safety. This practice generally involves from substitution or inferior, unrelated, or harmful raw drugs/raw materials (RM), often driven by various factors like scarcity of authentic materials, economic gain, or misidentification due to similar plant morphology. Nowadays, it is a significant concern in herbal medicine. Addressing adulteration requires a collaborative effort among regulatory bodies, industry stakeholders, and consumers to ensure the safety and efficacy. Material and Methods: Marketed samples were analyzed since a decade using modern tools (Taxonomy, Anatomy, Powder Microscopy, and Chemometrics) as physical markers for the identification and validation. Available published literature, compendium, floras, and monographs were extensively studied to mitigate the misidentification of herbal raw drugs. Results and Discussion: Out of 77 raw drugs/RM, 23 herbs, 10 climbers, 23 shrubs, and 22 tree species were identified as marketed adulteration. Among the plant part use/raw drugs, 29 root, 06 stem bark, 05 whole plant, 05 rhizomes, 05 flowers, 03 heartwood, 03 leaves, 03 tubers, and rest were recorded as aerial part, bark, seeds, galls, resin, and stamens, respectively. Strengthening stringent regulations and quality control measures can help to prevent Ayurvedic adulteration. Educating all stakeholders, for example, aggregators, collectors, suppliers, manufacturers, and consumers about the importance of commercial cultivation and using the authentic herbal raw drugs/extracts. Mitigation plan has been suggested as commercial cultivation (54 species), alternative plant part use approvals (09 spp), alternative plant species approvals (06 spp), and regulatory approvals (08 spp) from Ayurvedic Pharmacopoeia of India.